Comparison manual and CVT transmission for a car under 1 liter engine - Mohammad Azlan, Abdul Aziz (2010)
This thesis presented about comparison manual and CVT transmission. This thesis deals with analysis on performance of transmission for a car under 1 liter engine. The objective of this thesis is to compare the performance of transmission between manual transmission and CVT transmission. Besides that, the purpose of this thesis is to analyze the performance of the Manual Transmission and the CVT Transmission for a car under 1 liter engine. This thesis also purposes to study the suitability using CVT for a car under 1 liter engine. Manual transmission and CVT transmission have their own advantages and one of that is better in their performance. In performance, there are many category that compared consist of power available, tractive force, fuel consumption and many more. The data used for the analysis is obtained through calculation using specification data that has got from brochure which is downloaded from Toyota’s official web because this model only market at Europe. This model fulfilled this project because it had two types of transmission which is CVT transmission and Manual Transmission. The post-processing method was performed using manual calculation with certain engineering formula and graph is plotted by using assistance software such as Microsoft Excel. The post-processing method to analyze the performance of transmission was performed using the SAE definition. From the results, it is observed that the performance of CVT is better than manual transmission. It is also observed that Manual Transmission is better than CVT in term of fuel consumption for a car under 1 liter engine. Besides that, CVT are suitable to use for a car under 1 liter engine because it gives more power and ride comfort ability. Future work, this comparison between manual transmission and CVT must do in experimental or simulation since CVT technology just begun to blossom to Malaysia. There are many factors that required to do research by experimental especially in transmission’s performance and driveability.